Pengembangan Tes Berbentuk Gambar Mengenai Materi Mitigasi Dan Adaptasi Bencana Alam Bagi Kelas X - Hestiyaningsih, Aryanti Ristin; , Dra. Siti Taurat Aly, M.Pd (2015)
Evaluation of learning which is the end of a learning process has a very important role for students and teachers to determine whether the purpose of learning has been achieved or not. Material mitigation and adaptation to natural disasters is one of the material taught in order to achieve competence 3.7 is to analyze mitigation and adaptation to natural disasters with the study of geography. This study has three objectives: 1) Knowing how the test criteria form the desired image by students regarding the matter of mitigation and adaptation to natural disasters for class X. 2) Developing the evaluation of learning about the materials natural disaster mitigation and adaptation for class X. 3) Determine the effectiveness of the test shaped picture on the material of natural disaster mitigation and adaptation for class X. Researc Research and Development (R & D) by using a model of Dick and Carrey. The study was conducted at SMA Muhammadiyah 1 Surakarta to retrieve data needs analysis, product trials, and experimental tests in the form of images. The sampling technique using cluster random sampling.Teknik data collection using interviews, questionnaires, and tes.Hasil from this research that the test product in the form of images made in accordance with the needs of students and has been validated by experts and has been tested. Results of experimental tests in the form of images obtained from post-test on the experimental class and control class that is based on the KKM geography class X SMA with a value of 7.5 indicates the experimental class there are 10 students who score below KKM and control classes totaling 13 students It can be concluded that the development of effective use in learning.